Spatial and multi-level analysis of factors associated with long-acting reversible modern contraceptive use among married women in Ethiopia - Bezawit Adane; Bereket Kefale; Elsabeth Addisu; Mastewal Arefaynie; Kefale Mitiku; Yitayish Damtie; Tilahun Degu Tsega; Amare Agmas Andualem; Mahider Awoke Belay; Getachew Tadesse Bedane; Natnael Kebede; Yitbarek Wasihun; et al. (PLoS ONE, 2025)
Background Despite the increasing global use of modern contraceptives, the utilization of Long-Acting Reversible Contraception (LARC) remains low in Sub-Saharan Africa, particularly in Ethiopia, where less than 3% of women use LARC. This low usage is associated with high rates of maternal and under-five morbidity and mortality, contrasting with the global average utilization rate of 15%. Previous studies have found a significant association between marital status and LARC usage, but there is a lack of understanding regarding other individual and community-level factors that may influence this utilization. Additionally, many of the previous studies were either localized or had limited sample sizes, failing to account for spatial variations and clustering effects. In light of these gaps, this study aims to investigate the spatial and multilevel factors from nationally collected data to identify the individual and community-level factors associated with LARC usage among married women in Ethiopia. Methods The study employed a cross-sectional design, utilizing secondary analysis of data from the 2019 Ethiopian Mini Demographic and Health Survey (EMDHS). The sample included 5,743 married women; selected using a two-stage stratified sampling technique. Data analysis was conducted with the verification of basic assumptions for multilevel logistic regression. The study utilized spatial and multilevel mixed effect model analysis. To demonstrate the strength and direction of associations, Adjusted Odds Ratios (AOR) with 95% confidence intervals were used. Result The study findings revealed significant associations with LARC usage in Ethiopia based on individual-level and community-level variables. Individual-level variables: Older age group was negatively associated with LARC use, (AOR = 0.28, 95%CI = 0.12, 0.64), higher education level was positively associated with LARC use (AOR = 2.99, 95%CI = 1.82, 4.92). Community-level variables: Communities with high female educational status (AOR = 1.75, 95%CI = 1.10, 2.76), communities with higher wealth were also positively associated with LARC use (AOR = 1.92, 95%CI = 1.15, 3.20). Living in Somali region was negatively associated with LARC use, indicating that women residing in this region had a significantly lower likelihood of using LARC (AOR = 0.03, 95%CI = 0.00, 0.33). Overall, these results highlight the influence of both individual-level and community-level factors on LARC utilization among married women in Ethiopia. Conclusions Age, educational attainment, community-level female education, community-level wealth, and region were identified as significant predictors of Long-Acting Reversible Contraceptive (LARC) use. Based on these findings, it is recommended that policies be implemented to enhance women’s education across various levels of the population. Special attention should be directed towards the most economically disadvantaged population, and efforts should focus on strengthening the health-seeking behaviors of the people. To improve contraceptive rates, regions with low utilization should be targeted for the expansion of tailored services that align with the lifestyles of their populations.